Can mycophenolate mofetil be an effective option in the treatment of vascular Behçet's Syndrome - Uslu, Emine; Göveç Giynaş, Nilgün; Karaman Ongun, Zehra; Sezer, Serdar; Yayla, Müçteba Enes; Turgay, Tahsin Murat; Ateş, Aşkın (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background/AimBehcet’s syndrome (BS) is a type of vasculitis that primarily affects veins and tend to involve pulmonary arteries more often than peripheral arteries or the aorta. Inflammation is a central role in the development of thrombotic events in BS.  Given its critical role in etiopathogenesis, the use of immunosuppressive therapy is fundamental to the treatment strategy.The aim of our study is to report our center's experience with mycophenolate mofetil (MMF) treatment in vascular BS (VBS) patients.Materials and MethodsThe clinical, laboratory and imaging findings of the patients receiving MMF treatment for vascular BS were retrospectively evaluated.  It was noted whether MMF treatment was induction or maintenance treatment. Treatment related side effects were noted. On the 12th month, patients were evaluated for the development of new events and being in remission.ResultsFive patients underwent MMF treatment for remission induction, while another five patients received MMF for maintenance. Relapses occurred in 2 out of 5 patients who were administered MMF as induction therapy, resulting in the development of acute deep vein thrombosis. Among the five patients receiving MMF as maintenance treatment, only one exhibited an active vascular event. Additionally, one patient was classified as vascularly active based on a CRP level of 10.3 mg/l.ConclusionMMF therapy may be an effective and safe treatment agent that can be preferred as azathioprine and cyclosporine in VBS patients, especially in maintenance therapy. This study is the first investigation into MMF treatment in patients with vascular BS.